2020
DOI: 10.18196/jai.2101134
|View full text |Cite
|
Sign up to set email alerts
|

Green Earth: Carbon Emissions, ISO 14001, Governance Structures, Militarily Connected from the Manufacturing Industries in Indonesia

Abstract: Research aims: This study aims to examine the effect of ISO 14001 empirically, Governance Structures and companies led by back with a military to carbon emissions disclosure in the manufacturing company that registered at the (IDX) Indonesian Stock Exchange of 2013 to 2017. Design/Methodology/Approach: The sample in this research was 53 companies chosen based on purposive sampling technique. The data used was 265 observation. The testing of hypotheses uses Ordinary Least Square (OLS) regression with STATA v14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Harymawan's (2018) research conducted in Indonesia found that companies that have leaders with a military background have the power to get low-interest rates and have low debt. The results of this study are in line with Iswati and Setiawan, (2020) stated that military connections have no influence on the disclosure of carbon emissions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Harymawan's (2018) research conducted in Indonesia found that companies that have leaders with a military background have the power to get low-interest rates and have low debt. The results of this study are in line with Iswati and Setiawan, (2020) stated that military connections have no influence on the disclosure of carbon emissions.…”
Section: Resultssupporting
confidence: 90%
“…This can be due to several factors, one of which is to make voluntary reporting requires considerable costs and a long time to be made which aims to be used by stakeholders in analyzing and making decisions. In line with the research of Yunus et al, (2016); Iswati and Setiawan (2020).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…According to Supatminingsih (2015), ISO 14001 certified companies are committed to continuous and sustainable improvement. The implementation of ISO 14001 also represents a good environmental management system, where the company is committed to monitoring, managing, controlling, and reporting related to operational activities related to environmental aspects (Iswati & Setiawan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…, (Monica dkk, 2021) Accounting Analysis Journal AAJ (Akhiroh & Kiswanto, 2016), (Krisnawanto & Solikhah, 2020), (Hapsari & Prasetyo, 2020) Journal of Accounting and Investment JoAI (Hapsoro & Falih, 2020), (Iswati & Setiawan, 2020) Indonesian Journal of Sustainability Accounting and Management IJSAM (Setiawan & Iswati, 2019), (Daromes dkk, 2020), (Evana dkk, 2021) The…”
mentioning
confidence: 99%